Accounting For Governmental and Nonprofit Entitiesm - Wilson, Earl Ray (Irwin, 2007)
The 15th edition of Accounting for Governmental and Nonprofit Entities is a comprehensive governmental and not-for-profit accounting text that balances concepts and procedures written by accounting professors engaged with professional for students who will be auditing and working in public and not-for-profit sector entities. This market leading text brings instructors and students a comprehensive knowledge of the specialized accounting and financial reporting practices of governmental and not-for-profit organization, and how those organizations can better meet the information needs of a diverse set of financial statement users and decision makers. With the extensive experience of the current author team comes along a relevant and accurate new edition as well as instructor tools.